When to Not Respond in Kind? Individuals' Expectations of the Future and Their Support for Reciprocity in Foreign Policy - Osman Sabri Kiratli; Sabri Arhan Ertan (Political Behavior, 2024)
This paper investigates if individuals' negative assessments of the future drive micro-level reluctance for international cooperation and reciprocal behavior, a core principle of multilateralism. To test our theoretical expectations, we field online survey experiments on a sample of over 3000 respondents in the US and Turkey in October–November 2020. The experimental results show that on average, individuals are fairly sensitive to target countries' policy actions and are inclined to reciprocate when contemplating whether to increase contributions to UN or consent to bilateral trade liberalization. Yet, further analyses concur that individual inclinations to reciprocate are substantially moderated by their future expectations. Specifically, individuals who are more pessimistic about their material prospects remain fairly indifferent to the positive actions of other countries, but are more likely to penalize negative foreign policy actions by reciprocating in kind.
doi:10.7910/DVN/CCSETI
Keywords: 320; International cooperation; Reciprocity; Public opinion; International institutions; Trade liberalization